2013
DOI: 10.1007/s10461-013-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

How Does Antiretroviral Treatment Attenuate the Stigma of HIV? Evidence from a Cohort Study in Rural Uganda

Abstract: Program implementers and qualitative researchers have described how increasing availability of HIV antiretroviral therapy (ART) is associated with improvements in psychosocial health and internalized stigma. To determine whether, and through what channels, ART reduces internalized stigma, we analyzed data from 262 HIV-infected, treatment-naïve persons in rural Uganda followed from ART initiation over a median of 3.4 years. We fitted Poisson regression models with cluster-correlated robust estimates of variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 59 publications
9
79
4
Order By: Relevance
“…Antiretroviral drugs improve general well-being and physical health of HIV-infected patients and the use of ART is known to reduce HIV-related stigma. 22 In one study, stigma and discrimination was eliminated after initiating of ART with some participants reporting about friends and families "returning to them" and "apologizing for abandoning" them once they started "looking well." 23 In studies conducted mainly in developed countries, negative outcome to disclosure was commonest among unmarried sexual partners, sero-discordant couples, and patients with low economic status, especially Africa Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Antiretroviral drugs improve general well-being and physical health of HIV-infected patients and the use of ART is known to reduce HIV-related stigma. 22 In one study, stigma and discrimination was eliminated after initiating of ART with some participants reporting about friends and families "returning to them" and "apologizing for abandoning" them once they started "looking well." 23 In studies conducted mainly in developed countries, negative outcome to disclosure was commonest among unmarried sexual partners, sero-discordant couples, and patients with low economic status, especially Africa Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Six articles reported on prospective cohort data (Cuca et al, 2012;Makoae et al, 2009;Peltzer, 2012;Tsai, Bangsberg, Bwana, et al, 2013;Wagner, Ghosh-Dastidar, Garnett, Kityo, & Mugyenyi, 2013) and one reported on both prospective cohort data and cross-sectional data (Pearson et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Within facilities, five studies used total or random sampling of participants (Cuca et al, 2012;Pearson et al, 2009;Takada et al, 2014;Tsai, Bangsberg, Bwana, et al, 2013;Wagner et al, 2013); one used purposive sampling (Cloete et al, 2008); and five used convenience sampling (Kalichman et al, 2009;Neuman & Obermeyer, 2013;Sorsdahl et al, 2011;Visser et al, 2008;Visser & Sipsma, 2013). The remaining six articles did not report methods used to sample participants within facilities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations